2013
DOI: 10.1097/ico.0b013e31829b21d1
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Pattern of Tear Osmolarity and Its Relationship to Corneal Thickness and Deswelling

Abstract: TitleResults: The tear film upon wakening (264 6 14 mOsm/L) was hypoosmotic compared with baseline (297 6 15 mOsm/L, P , 0.001). TO (in mOsm/L) at 20 minutes, 40 minutes, 1 hour, 2 hours, 4 hours, and 8 hours were 287 6 10, 292 6 16, 293 6 12, 292 6 10, 289 6 10, and 286 6 10, respectively. CCT (mean 6 SD) at baseline was 552.2 6 35.9 mm and increased to 572.0 6 38.7 mm after sleep. CCT returned to baseline thickness 4 hours after awakening (P , 0.000) and remained stable throughout the day. A small but statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 19 publications
4
56
0
Order By: Relevance
“…Historical meta-analyses of tear osmolarity using laboratory-based freezing point osmometers report specificities of upward of 94% for the marker as a whole 15. In normal subjects with a healthy lacrimal system, repeated testing has been shown to have little to no effect on the measured tear osmolarity 12,28. Insofar that the recruited subjects are truly devoid of dry eye disease, an accurate osmometer is expected to report the majority of test results below the established cutoff for dry eye disease.…”
Section: Discussionmentioning
confidence: 99%
“…Historical meta-analyses of tear osmolarity using laboratory-based freezing point osmometers report specificities of upward of 94% for the marker as a whole 15. In normal subjects with a healthy lacrimal system, repeated testing has been shown to have little to no effect on the measured tear osmolarity 12,28. Insofar that the recruited subjects are truly devoid of dry eye disease, an accurate osmometer is expected to report the majority of test results below the established cutoff for dry eye disease.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that there is no ethnicity-related difference in the relationship between osmolarity and corneal thickness. 44 However, there is a clinically significant difference in CCT among different ethnic groups. For example, on average, African Americans have a thinner CCT when compared with whites.…”
Section: Corneamentioning
confidence: 99%
“…[45][46][47] Other studies have demonstrated that Asians have a thicker CCT than African Americans, but little-to-no difference when compared with a Hispanic or white populations. 44,48,49 Given these inherent ethnicity-related differences in CCT, it is imperative to determine the individual magnitude of change in CCT before and after an intervention (e.g., contact lens wear) to determine its safety and efficacy. In studies where corneal edema is used as a "safety" index (e.g., development of prototype contact lenses or assessment of contact lens oxygen-transmissibility effects on corneal thickness), simply comparing group means can be misleading because withinsubject variability and the range of magnitudes of individual changes in CCT from preintervention to postintervention are not taken into account.…”
Section: Corneamentioning
confidence: 99%
“…9 Furthermore, physiological diurnal fluctuations in tear osmolarity have been shown to correlate with changes in central corneal thickness (CCT) in human eyes, as quantified using high-resolution anterior segment optical coherence tomography (OCT). 10 Preliminary evidence also suggests that individuals with clinical signs and symptoms of DED have reduced corneal thickness 11 and endothelial cell changes, 12 although the potential effect of tear osmolarity per se was not considered in these studies.…”
Section: Introductionmentioning
confidence: 99%